Pendampingan analisis standar belanja: Pengendalian anggaran dan kinerja Pemerintah Kabupaten Konawe Kepulauan Tahun 2019 - Rahmawati; Marwah Yusuf (P3HKI - Universitas Muhammadiyah Parepare, 2021)
This service discusses assistance in preparing the Expenditure Standard Analysis (ASB) within the Konawe Islands Regency Government in 2019. The aim is to increase understanding of the factors that influence the amount of proposed spending and performance indicators in ASB. The implementation method includes secondary and primary data collection and analysis using the Ordinary Least Square (OLS) method. The results showed that this mentoring activity succeeded in providing an in-depth understanding to partners regarding the factors that affect the amount of proposed expenditure, such as differences in types of activities, performance targets, steps to complete activities, and activity needs: expenditure objects, unit prices, and the basis for subtraction and calculation of proposed expenditures. In addition, partners also gain a better understanding of performance indicators in ASB, including inputs, outputs, efficiency, quality, and results. The practical implementation of this science is proven in preparing ASB for office stationery procurement activities, where partners can control costs more effectively and allocate budgets as needed. In conclusion, this mentoring activity provides significant benefits in increasing budget management capacity at the local level. Collaborative efforts and mentoring between local governments and partners must continue to achieve more inclusive and sustainable development goals in public budget management.